Redox-Responsive Transcription Factor 1 (RRFT1) Is Involved in Extracellular ATP-Regulated Arabidopsis thaliana Seedling Growth. (12th February 2020) - Zhu, Ruojia; Dong, Xiaoxia; Xue, Yingying; Xu, Jiawei; Zhang, Aiqi; Feng, Meng; Zhao, Qing; Xia, Shuyan; Yin, Yahong; He, Shihua; Li, Yuke; Liu, Ting; et al.
Abstract: Extracellular adenosine triphosphate (eATP) is an apoplastic signaling molecule that plays an essential role in the growth and development of plants. Arabidopsis seedlings have been reported to respond to eATP; however, the downstream signaling components are still not well understood. In this study, we report that an ethylene-responsive factor, Redox-Responsive Transcription Factor 1 (RRTF1), is involved in eATP-regulated Arabidopsis thaliana seedling growth. Exogenous adenosine triphosphate inhibited green seedling root growth and induced hypocotyl bending of etiolated seedlings. RRTF1 loss-of-function mutant ( rrtf1 ) seedlings showed decreased responses to eATP, while its complementation or overexpression led to recovered or increased eATP responsiveness. RRTF1 was expressed rapidly after eATP stimulation and then migrated into the nuclei of root tip cells. eATP-induced auxin accumulation in root tip or hypocotyl cells was impaired in rrtf1 . Chromatin immunoprecipitation and high-throughput sequencing results indicated that eATP induced some genes related to cell growth and development in wild type but not in rrtf1 cells. These results suggest that RRTF1 may be involved in eATP signaling by regulating functional gene expression and cell metabolism in Arabidopsis seedlings.